Innovative technologies for growing digital maturity in auditors - N. V. Ruban-Lazareva (Вестник университета)
The changeable, unknown, complex, and multivalent world embraced by innovations makes new demands on auditors’ professional competencies, which are inseparable from the mastery of technologies. Innovative auditing technologies of regional finance and real economy auditing have been analyzed to substantiate the value of auditors’ digital maturity in the diversity of such technologies. Quantitative methods based on statistical studies confirmed the growth of audit, control, expert analytical activities, and the need to implement innovative technologies for greater coverage of the control data set. Innovative technologies used in audit practice have been presented. The definition of digital maturity in an auditor has been given, which substantiates the need for continuous training in modern technologies such as digital inspector of state and municipal financial audit, conducting and accounting of general audit results, and processing of huge arrays of reporting data, analytical dashboards, and tools for checking counterparties using the analysis of their debts and risks. Digital maturity has been proposed to be assessed by considering digital culture, professional knowledge, skills and competencies of tool ownership, and process thinking in quality data collection implementation during the udit. The planning, execution, and automation of audit control activities with innovative technologies create the basis for prompt effective management of the entire process, company resources, and regional finances. Visualization of the reporting verification results provides for their visibility for users in order to immediately make management decisions aimed at sustainable financial development.